The Effects of Inventory Turnover and Accounts Receivable Turnover on Liquidity - Umami, Alvario Ridho; Silvia, Dewi; Khoirina, Siti; Alvario Ridho Umami; Dewi Silvia; Siti Khoirina (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to determine the influence of inventory turnover and accounts receivable turnover variables (X) on the liquidity of cigarette industry companies listed on the IDX in 2020 – 2022 (Y). This study employed quantitative research methods. The data collecting technique used was purposive sampling, which obtained four samples. The analysis model used was regression analysis using SPSS 2019 data processing tools. The analysis shows that inventory turnover has a positive effect on liquidity, accounts receivable turnover has a positive effect on company liquidity, and inventory turnover and accounts receivable turnover simultaneously influence company liquidity